Potential Application of Carbon Quantum Dots (CQD) Synthesis from Rice Husk Waste Composite as Advanced Solar Cells to Increase Photon Energy Absorption in Maximizing Solar Panels Power Output Production - Adnan Hasyim Wibowo; Stella Eulia Andoko; Ilham Arya Satya (NBRI Press, 2023)
The increase in national energy consumption has forced us to intensify renewable energy utilization. Solar panel is one optional answer for that purpose. Unfortunately, the product resistance and photon absorption from silicon-based solar cells are still not good enough. Carbon quantum dots (CQD) could be an alternative advanced material that can be utilized to maximize the performance of solar panels. Therefore, researchers are interested in finding out how to manufacture CQD from the synthesis of rice husk waste composite as an advanced solar cell and analyze its potential to maximize solar panel photon energy absorption. Researchers use mixed study that applies literature review methods (as part of the descriptive research aspect) and causal comparative research methods (as part of the quantitative aspect). Based on previous research, rice husk waste was pre-processed by washing using de-ionized water (DI water) to remove residue, then baked and blended into powder, and cleaned using HCl as impurities remover. The hydrothermal process was carried out at 190 oC for 12 hours to synthesize CQD which functioned by amino and carboxyl. For further purification, CQD was dialyzed against DI water in cellulose. Super-dense material due to quantum level compression, makes CQD have a higher resistance when compared to silicon as solar cells. In addition, the absorption of photon energy that can be done by CQD solar cells has a higher percentage when compared to conventional solar cells. However, in this paper, the researchers did not make CQD and only analyzed through modeling which became the research gap in this paper.